Developing anti-bullying cultures in primary schools: what can head teachers do to ensure successful anti-bullying cultures? - Brewer, Lesley (2018)
Bullying in schools is a widespread problem, attracting a great deal of interest and publicity in recent years. The negative impacts of bullying can have consequences for not just the victims, but also for the school, perpetrators and wider community members. Such consequences can be experienced instantaneously and/or at a subsequent time, often in later life.